Coordination complexes constructed from pyrazole–acetamide and pyrazole–quinoxaline: effect of hydrogen bonding on the self-assembly process and antibacterial activity. Issue 9 (14th February 2022) - Chkirate, Karim; Karrouchi, Khalid; Chakchak, Hind; Mague, Joel T.; Radi, Smaail; Adarsh, N. N.; Li, Weiyang; Talbaoui, Ahmed; Essassi, El Mokhtar; Garcia, Yann
Abstract : Two mononuclear coordination complexes of N -(2-aminophenyl)-2-(5-methyl-1 H -pyrazol-3-yl)acetamide (L1 ) and one mononuclear complex, obtained after in situ oxidation of L1, have been synthesized and characterized spectroscopically. Abstract : Two mononuclear coordination complexes of N -(2-aminophenyl)-2-(5-methyl-1 H -pyrazol-3-yl)acetamide (L1 ), namely [Cd(L1 )2 Cl2 ] (C1 ) and [Cu(L1 )2 (C2 H5 OH)2 ](NO3 )2 (C2 ) and one mononuclear complex [Fe(L2 )2 (H2 O)2 ](NO3 )2 ·2H2 O (C3 ), obtained after in situ oxidation of L1, have been synthesized and characterized spectroscopically. As revealed by single-crystal X-ray diffraction, each coordination sphere made of two heterocycles is completed either by two chloride anions (in C1 ), two ethanol molecules (in C2 ) or two water molecules (in C3 ). The crystal packing analysis of C1, C2 and C3, revealed 1D and 2D supramolecular architectures, respectively, via various hydrogen bonding interactions, which are discussed in detail. Furthermore, evaluation in vitro of the ligands and their metal complexes for their antibacterial activity against Escherichia coli (ATCC 4157), Pseudomonas aeruginosa (ATCC 27853), Staphylococcus aureus (ATCC 25923) and Streptococcus fasciens (ATCC 29212) strains of bacteria, revealed outstanding results compared to chloramphenicol, a well-known antibiotic, with a normalized minimum inhibitory concentration as low as 5 μg mL −1 .